Impact Of Quality Courseware on Effective E-Learning - Saif M. Duhaim; Zahraa H. Ghadhban (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
Courseware is an effective and important teaching and learning model, and it is at the core of the process of creating e-learning. The objective of this paper is to show effect of quality courseware on effective e-learning. A quantitative research approach by questionnaire has been utilized. A total 90 participants have been surveyed with the use of the questionnaire. This study shows that quality courseware was the most significant positive factor and more import e learning success.